If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5m + -26 = -25 + 6m Reorder the terms: -26 + 5m = -25 + 6m Solving -26 + 5m = -25 + 6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6m' to each side of the equation. -26 + 5m + -6m = -25 + 6m + -6m Combine like terms: 5m + -6m = -1m -26 + -1m = -25 + 6m + -6m Combine like terms: 6m + -6m = 0 -26 + -1m = -25 + 0 -26 + -1m = -25 Add '26' to each side of the equation. -26 + 26 + -1m = -25 + 26 Combine like terms: -26 + 26 = 0 0 + -1m = -25 + 26 -1m = -25 + 26 Combine like terms: -25 + 26 = 1 -1m = 1 Divide each side by '-1'. m = -1 Simplifying m = -1
| 5x^2-40x^2+75x= | | 3(5x+1)+6(5x+1)=2 | | .8m-.2m=9 | | 2x^4-3x^3+2x^2-15x+14=0 | | u^2-6u+8=0 | | -32xy^5+40x^3y^5-16xy^5= | | 8y=7y-45 | | 3t^3-9t+6=0 | | 27c^4-125c=0 | | 9x^2-5x=3 | | -8=-x-4 | | 3x=2-4y | | 10y=5y-5 | | 4(3x+4)=52 | | 35x^2-16x-3=0 | | 4x+3=-45 | | 9x+14=-67 | | w^2+4w-x^2+4=0 | | -7y+5(y-4)=-18 | | 6x+13=-5 | | 2x-0.35=.20 | | 4x+6=-62 | | 7(4x+1)=3(12x-3) | | 92x+31=72 | | -3x+9=30-6x | | 2c/10=24 | | (5c+6)(5c-6)=0 | | 2x^2-4x-44=0 | | 53a-143=42a+8 | | 3x=6-x | | 18-t/20=-9 | | 3s/5=-21 |